2002
DOI: 10.1182/blood.v99.1.319
|View full text |Cite
|
Sign up to set email alerts
|

Primitive, quiescent, Philadelphia-positive stem cells from patients with chronic myeloid leukemia are insensitive to STI571 in vitro

Abstract: In clinical trials, the tyrosine kinase inhibitor STI571 has proven highly effective in reducing leukemic cell burden in chronic myeloid leukemia (CML). The overall sensitivity of CML CD34 ؉ progenitor cells to STI571 and the degree to which cell death was dependent on cell cycle status were determined. Stem cells (Lin ؊ CD34 ؉ ) from the peripheral blood of patients with CML in chronic phase and from granulocyte-colony-stimulating factor-mobilized healthy donors were labeled with carboxy-fluorescein diacetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
886
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,093 publications
(938 citation statements)
references
References 35 publications
34
886
3
7
Order By: Relevance
“…Once more data of stop patients becomes available, the theory might have to be revised, but the conclusion that leukemic stem cells cannot be depleted by imatinib can safely be drawn based on the available information. Additionally, previous work has shown that CML stem cells are insensitive to imatinib in vitro (Graham et al, 2002).…”
Section: Model Dynamicsmentioning
confidence: 98%
“…Once more data of stop patients becomes available, the theory might have to be revised, but the conclusion that leukemic stem cells cannot be depleted by imatinib can safely be drawn based on the available information. Additionally, previous work has shown that CML stem cells are insensitive to imatinib in vitro (Graham et al, 2002).…”
Section: Model Dynamicsmentioning
confidence: 98%
“…On the contrary, there are data suggesting an inability of TKIs to eliminate precursor CD34 þ CML cells. 17 Moreover, there are reports of disease relapse following achievement of CMR on TKI-based therapy. [18][19][20] Currently, the only treatment modality available to CML patients that is considered potentially curative is allogeneic stem cell transplantation, which may induce remission via elimination of CML stem cells through a graft vs leukemia effect.…”
Section: Second-generation Tki's In the Front-line Setting: Molecularmentioning
confidence: 99%
“…Indeed, recent data suggest that imatinib may not achieve complete ablation of CML cells 217 , and even patients with CML who present complete molecular response almost invariably relapse when the drug is discontinued 216,218 . These observations may be explained by in vitro findings suggesting that ima- tinib, which is very active against differentiated CML progenitors, shows limited activity against CML stem cells [219][220][221] . Unequivocal in vivo proof of the resistance of leukemic stem cells to imatinib was recently provided by Sanchez-Garcia et al 222 .…”
Section: Cancer Stem Cells From a Therapeutic Perspectivementioning
confidence: 99%